Assessment of nutritional value and investigation of biological activities of Hylocereus costariscensis - Md. Mostafa Hossain; Mohammad Shoeb (Current Research on Bioscences and Biotechnology, 2023)
Hylocereus costariscensis (Dragon fruit), an edible cactus species of the Cactaceae family, is rich in essential nutrients like antioxidants, dietary fibers, minerals, and vitamins. The aim of the study was to analyze the proximate composition and investigate the biological activities of the edible parts (flesh and seed) of H. costariscensis cultivated in Bangladesh. Air-dried fruits were successively extracted by n-hexane, dichloromethane, and methanol. The moisture and ash contents of the fruits were found to be 85.95 ± 0.53% and 0.99 ± 0.02%, respectively. UV and FT-IR spectral analysis showed the presence of different functional groups, which might be due to the presence of fatty acids, alkaloids, terpenoids, and phenolic compounds. The total carbohydrate content was 10.52g/100g as determined by the modified Molisch method. Fatty acid analysis revealed the presence of octanoic acid (5%), palmitic acid (16%), octadecanoic acid (41%), cis-9-oleic acid (29%), and linoleic acid (6%). The total phenolic content of different extracts was determined by the Folin–Ciocalteau method, and the value was found to be higher in the methanol extract (151.05 ± 0.34 mg GAE/g) than in the other two extracts. Total flavonoid content and total antioxidant content were determined by the aluminum chloride method and the phosphomolybdate assay, respectively. The methanol extract exhibited the highest activities (91.54 ± 0.22 mg QE/g and 40.08 ± 0.21 mg AAE/g, respectively) among all extracts in both cases.